25th Anniversary Article: Recent Advances in n‐Type and Ambipolar Organic Field‐Effect Transistors. (27th August 2013) - Zhao, Yan; Guo, Yunlong; Liu, Yunqi
Abstract The advantages of organic field‐effect transistors, such as low cost, mechanical flexibility and large‐area fabrication, make them potentially useful for electronic applications such as flexible switching backplanes for video displays, radio frequency identifications and so on. A large amount of molecules were designed and synthesized for electron transporting (n‐type) and ambipolar organic semiconductors with improved performance and stability. In this review, we focus on the advances in performance and molecular design of n‐type and ambipolar semiconductors reported in the past few years.